Increased risk of short‐term depressive disorder after Helicobacterpylori eradication: A population‐based nested cohort study. Issue 4 (11th June 2021) - Tsai, Chia‐Fen; Chen, Mu‐Hong; Wang, Yen‐Po; Liu, Pei‐Yi; Hou, Ming‐Chih; Lee, Fa‐Yauh; Lu, Ching‐Liang
Abstract: Background: Depressive disorder is a major psychiatric illness, and a disturbed brain‐gut‐microbiome axis may contribute to its pathophysiology. Chronic Helicobacter pylori ( H . pylori) infections are common in the general population and using multiple antibiotics is required for its eradication, which is associated with gut dysbiosis and may lead to depression. We aimed to evaluate the risk of psychiatrist‐diagnosed depression in patients with peptic ulcer diseases (PUD) receiving anti‐ H . pylori therapy. Materials and methods: We collected data from the National Health Insurance Research Database (NHIRD) in Taiwan on PUD patients undergoing antibiotic treatment for H . pylori infection; patients and controls were matched for age, sex, income, level of urbanization, and comorbidities. Results: Of the 1 million beneficiaries in the NHIRD, we identified 7087 patients for inclusion in the eradication cohort and 7087 matched non‐eradication controls with PUD. Antibiotic therapy is associated with a short‐term (<30 days) increase in the incidence of psychiatrist‐diagnosed depressive disorder ( p = 0.009, after multiple comparisons with Bonferroni correction) in the eradication cohort compared with the controls. Female (OR: 4.55, 95% CI: 1.53–13.48) PUD patients were more likely to display an increased risk of depression within 30 days after eradication therapy. Clarithromycin use was related to an elevated likelihood (OR: 3.14, 95% CI: 1.45–6.80) of subsequent depressive disorder within 30 days after eradication therapy. Conclusions: Antibiotic eradication treatment for H . pylori infection is associated with a significant short‐term (less than 30 days) increase in the incidence of psychiatrist‐diagnosed depressive disorder, which can be overlooked by gastroenterologists and general practitioners.